Disaster management and recovery preparedness for the University of the Philippines School of Labor and Industrial Relations (U.P. SOLAIR) Library - Sarmiento, Chester Bryan P.; Arlante, Salvacion M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
A disaster is a sudden calamitous event producing great material damage, loss and distress (Macleish). In this time of paranoia going on around us, a lot of things can happen. There are two kinds of disaster. There is what we call man-made disasters like bomb threats, terrorism, sabotage, etc. and naturally occurring disasters like floods, fires (except in cases of arson), earthquakes etc. Most people experience various levels of disasters from a simple loss of a document to a great catastrophic event like fire, flood, earthquake, etc. In short, anybody and anything can be a victim of a disaster. The library can also be a victim and is not an exception. And when it is hit by a disaster, the damage that it could cause would be irreparable and totally devastating. This can be minimized though, if there is a well-planned procedure on what to do in case of disasters. This is where disaster planning comes in. Disaster control planning is concerned with the formulation of a written plan, which gives details of preventive, and preparatory measures intended to reduce potential risks in order to minimize the effects of disasters. The University of the Philippines School of Labor and Industrial Relations (UP SOLAIR) is located at the left wing of Bonifacio Hall. It provides support in teaching, research and extension services of the UP School of Industrial Relations. It offers library service to workers all over the country in the field of labor, industrial and human resources development.
The primary objective of this study was to determine if the UP SOLAIR library has an existing disaster management plan and to recommend or propose a disaster management plan if ever it doesn't have one. Target benefactors of this study were the library staff, faculty and other users of the UP SOLAIR library to ensure their safety at all times and to serve as a guideline on how to react in the advent of a disaster. Its implications were the research and the results that were produced and the value of having a disaster management plan with relation to the library set-up.
The results of this research were concluded by way of surveys on the awareness of library users and staff on various kinds of disasters, interviews by individuals who are highly credible and competent in their respective fields with respect to disaster management and participant observation on storage and preservation of library materials in the library. Through this the study, the researcher was able to come up with the following recommendations that would be beneficial to the library. From the fire safety inspection: Provide alternate remote exit door on the ground floor. Install additional remote automatic emergency lights for the second floor. Install at least three (3) smoke detectors in each floor. Install exit signs. From the electrical inspection: Circuit breakers have to be changed once every three years to maintain good quality of the flow of electricity. Regular inspection on electrical wirings. Regular inspection on electrical appliances. All electrical appliances should be turned off before vacating the building.
The study also proposed a disaster management plan for the University of the Philippines School of Labor and Industrial Relations (UP SOLAIR) as a guideline and set of procedures on what to do in the event of a disaster. It encompassed basic descriptions on how to handle library materials that are fire and water damaged.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Emergency management; University of the Philippines School of Labor and Industrial Relation Library